Comparative Effectiveness of 2-Dimensional Images, 3-Dimensional Fabricated Models, and Computer-Generated 3-Dimensional Images in Veterinary Anatomy Education - Carlton, Pamela G.; Kilroy, David; McCarney, Catherine; Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports, 2026)
Background: Anatomy education has traditionally relied on Two-Dimensional Images (2DI) and cadaveric dissections. However, newer modalities such as Three-Dimensional Fabricated Models (3DM) and Computer-Generated 3D Images (CG3DI) are increasingly being introduced. Comparative effectiveness evidence remains three dimensional limited. Objectives: This pilot study aimed to compare the impact of 2DI, 3DM, and CG3DI on student performance in veterinary anatomy. Materials and Methods: Twelve first-year Graduate Entry veterinary students were randomly allocated into three equal groups of four (n=4 Graduate Entry per group), each exposed to one of the teaching modalities for a 30-min study period. Pre- and post-intervention assessments, each comprising ten multiple-choice questions, were conducted to evaluate changes in performance. Results: Pre-test scores were similar across groups (2DI: mean 5.75/10, SD 0.96; 3DM: mean 5.75/10, SD 1.26; CG3DI: mean 6.00/10, SD 1.15). Post-test scores were: 2DI mean 6.00/10 (SD 2.16; mean change +0.25 questions, Cohen’s d=0.15); 3DM mean 5.75/10 (SD 1.50; mean change 0.00, Cohen’s d=0.00); CG3DI mean 5.25/10 (SD 1.26; mean change -0.75, Cohen’s d=-0.62). No statistically significant within-group or between-group differences were detected (Kruskal-Wallis H=1.63, p=0.44), consistent with the very small sample size. Conclusion: This pilot study suggests a trend toward score improvement with 2DI, no change with 3DM, and a modest decline with CG3DI over a brief study period. These non-significant findings, limited by the small sample, may inform a fully powered future study of a blended 2D/3D approach in veterinary anatomical education.
Keywords: Active learning; Anatomy Education; Educational Technology; Pedagogy; Simulation-based learning